Global increase of tropical cyclone precipitation rate toward coasts - Qi,W; Yong,B; Ritchie,EA; Tyo,JS; Toumi,R (Geophysical Research Letters, 2025)
Tropical cyclones (TCs) induced precipitation poses a critical threat to coastal regions. In the context of global warming and humidification, it remains to be clarified whether coastal exposure to TC-induced precipitation has a detectable response. Based on multi-source data sets in the past four decades, this study investigates the coastward trends of global TC-induced precipitation changes. We find that the TC lifetime maximum precipitation intensities show a statistically significant landward migration, moving about 30 km per decade. Furthermore, the precipitation intensities of TCs exhibit faster growth in coastal areas, with a concurrent rapid expansion of the land coverage of TC-induced precipitation. A consistent pattern of change is demonstrated between intensifying TC-induced precipitation and the warming-humidifying ambient environment, with higher significance in coastal areas. Our findings suggest that the spatial heterogeneity in global climate change may have contributed to the modulation of coastal TC-induced precipitation.